2018
DOI: 10.1145/3204455
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Deviations from Intended Routes Using Vehicular GPS Tracks

Abstract: This article proposes a method to find intersections at which cars tend to deviate from the optimal route based on global positioning system (GPS) tracking data under the assumption that such deviations indicate that car navigation systems (CNSs) and road signage are not readily available. If the intended route is known, deviations can be enumerated by comparing the intended route with the vehicle’s actual route as observed by a GPS; however, the intended route is unknown and can differ from the route suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…al [10] it was shown that among different routing preferences, almost half of the people preferred the fuel-efficient route, and only 18% and 3.5% preferred the fastest and shortest routes respectively. In addition, a couple of studies [11], [12] showed that a lot of people deviate from the recommended optimal route because of many reasons such as complex routes, inaccuracies in GPS [11], and unfamiliarity of the road, especially if the time is negligible [4]. In a study by Samson and Sumi, they reported that participants would only use the fastest route if it was 10 minutes faster.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al [10] it was shown that among different routing preferences, almost half of the people preferred the fuel-efficient route, and only 18% and 3.5% preferred the fastest and shortest routes respectively. In addition, a couple of studies [11], [12] showed that a lot of people deviate from the recommended optimal route because of many reasons such as complex routes, inaccuracies in GPS [11], and unfamiliarity of the road, especially if the time is negligible [4]. In a study by Samson and Sumi, they reported that participants would only use the fastest route if it was 10 minutes faster.…”
Section: Literature Reviewmentioning
confidence: 99%